Problems of book carrying in the works of Vaclovas Biržiška - Bronius Raguotis (Knygotyra)
The well-known bibliographer and historian of press Vadovas Biržiška (1884-1956) has addressed the problems of books' and periodicals' distribution and their functioning in many of his works.